Neck Management in cT1N0 Tongue Squamous Cell Carcinoma as Determined by Sonographic Depth of Invasion - Wu, Yao; Zhang, Xu; Dai, Liyuan; Fang, Qigen; Du, Wei (Frontiers in Oncology, 2022)
Objectives To compare the oncologic outcomes in patients with cT1N0 tongue squamous cell carcinoma (SCC) who underwent different neck management strategies stratified by sonographic depth of invasion (DOI). Methods The included patients were retrospectively enrolled, and divided into two groups: observation (OBS) and elective neck dissection (END). The regional control (RC) and disease-specific survival (DSS) rates were compared and stratified by sonographic DOI. Results The mean sonographic and pathologic DOIs were 3.8 and 3.7 mm, respectively; the two DOIs were significantly correlated (Spearman correlation coefficient 0.974. p <0.001). In patients with sonographic DOI <4.0 mm, the 5-year RC rates were 73 and 89% in the OBS and END groups, respectively, and were not significantly different. However, in patients with sonographic DOI ≥4.0 mm, the 5-year RC rate was significantly different between the OBS (57%) and END (80%) groups (p = 0.031). In patients with sonographic DOI <4.0 mm, the 5-year DSS rates were 79 and 89% in OBS and END groups, respectively, and were not significantly different. However, in patients with sonographic DOI ≥4.0 mm, the 5-year DSS rate was significantly different between the OBS (67%) and END (86%) groups (p = 0.033). Conclusions Sonographic DOI was notably correlated with pathologic DOI. Moreover, there was a significant survival difference between the OBS and END groups in cT1N0 tongue SCC patients with sonographic DOI ≥4.0 mm but not in those with sonographic DOI <4.0 mm. Our study provides a useful method to aid decision-making in the clinical setting for this patient group.